Characteristics of the Viqueque Formation in the Caraubalo Area, Viqueque District, Timor-Leste - M. Faustino; P. Setyo; Astuti B. S. (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
This research was conducted in the Cuha River, within the Buanurak area of Caraubalo Village, Viqueque District, Timor-Leste. The study area is geographically located between 08⁰49’29”S - 08⁰52'28”S and 126⁰23'8”E - 126⁰20'8”E. The objective was to characterize the facies of the Viqueque Formation through field data. The methodology involved measuring a stratigraphic cross-section, with subsequent analysis based on the parameters of the Bouma (1962), Walker (1979), and Mutti concepts. Analysis identified four main lithological units. Facies A1-A3 consist of gray marl, deposited by low-density turbidity currents in a lower fan setting (Td-Te Bouma intervals; F9a Fine Grain Facies). Facies B1-B2 feature interbedded sandstone and marl with parallel lamination, representing deposition in suprafan lobes (CT-2 sequence; F7 Fine Grain Facies). Facies C is characterized by normally graded conglomerates, interpreted as mid-fan channel deposits. Finally, Facies D comprises polymict conglomerates, deposited by high-density turbidity currents in an upper fan setting, corresponding to the CGL-7 facies (F9b) and the Ta Bouma interval.